Effect of near -symmetric potentials on nonlinear modes for higher-order generalized Ginzburg–Landau model. (1st December 2022) - Lin, Da; Dong, Kai-Ru; Zhang, Jia-Rui; Shen, Yu-Jia
Abstract: In this paper, we study the higher-order generalized Ginzburg–Landau model which contributes to describing the propagation of optical solitons in fibers. By means of the Hirota bilinear method, the analytical solutions are obtained and the effect of relevant parameters is analyzed. Modulated by the near parity-time-symmetric potentials, the nonlinear modes with 5% initial random noise are numerically simulated to possess stable evolution. Furthermore, the evolution of nonlinear modes is displayed through the adiabatical change of some parameters. The investigation of the present work is intended as a contribution to the work for the higher-order generalized Ginzburg–Landau model.